Internal Audit Function Quality and Audit Committees’ Practices: Survey Evidence from Jordan - Al Sawalqa, Fawzi Ata; Qtish, Atala (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The current study examines the extent to which audit committees comply with the requirements of corporate governance in Jordan and describes the current status of internal audit function. In addition, the study examines empirically the relationship between the internal audit quality and the compliance of audit committees with the governance requirements.<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> The results from 49 respondents indicate that audit committees comply with the requirement of <span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">corporate governance and no significant difference is found in such compliance due to sector. In addition, the internal audit quality attributes are met among Jordanian companies to a considerable extent. Further, the independence and objectivity dimension of internal audit quality has a positive and significant relationship with the compliance of audit committees with governance requirements. Internal audit competence and due professional care have no significant relationship with audit committees compliance. One important implication of the current study is the development of a scale to measure the compliance level of audit committees with the governance requirements that can be used by both academics and decision-makers in firms.